Inflation targeting in high inflation emerging economies: Lessons about rules and instruments - John B. Taylor (Journal of Applied Economics, 2019)
This talk emphasizes the connection between inflation targeting and monetary policy rules. Inflation targeting is not enough. You need to have a policy procedure - a policy rule - to achieve the target. And one cannot design or evaluate a monetary policy rule without a target inflation rate. Hence, there is a symbiotic relationship between inflation targeting and monetary policy rules. Initially, the instrument in the policy rule was a monetary aggregate - a quantity, usually the money supply. It was only later that research on monetary policy rules focused on another instrument of monetary policy - the interest rate, as velocity became more volatile so the interest rate was more reliable as instrument, at least for low levels of inflation. Interest rate rules work best within a band between very high inflation and deflation. Outside that band, the central bank should rely more on money growth rules.
Keywords: 330; Inflation targeting; interest rate rules; monetary policy instruments; monetary policy rules; money growth rules